Integrasi Manajemen Dan Etika Bisnis Islam Dalam Layanan Ibadah Umrah - Mochammad Ilham Hidayat; Taufiqur Rahman; Zainur Ridho (Iltizam : Jurnal Ekonomi dan Keuangan Islam, 2024)
This study aims to examine more deeply the service management and Islamic business ethics that exist at PT Nur Haramain mulia. The method used is descriptive qualitative, for research data collection includes observation, interviews, documentation. The results of this study indicate that PT Nur Haramain Mulia has an important task in serving pilgrims in making passports, providing rituals and the existence of mentors who are always there to make the Umrah worship of the jammah successful both in the country and in the holy land. Supporting factors and inhibiting factors must exist in an institution, some of the supporting factors in travel are adequate facilities and infrastructure, having many channels or enough cooperating parties to make PT. Nur Haramain Mulia Survive. And one of the inhibiting factors is that many pilgrims are from ordinary people who do not understand much about making passports and other files.